The Role of SME Managers' Personality Traits in Adapting to Changes and Demands Caused by the COVID-19 Pandemic - Stanislaw BRZEZINSKI (Communications of International Proceedings, 2021)
The COVID-19 pandemic wreaked havoc on the global economy, and the emerging chaos affected most businesses. When humanity will return to normality is unknown. Considering the situation, managers should now begin steering human capital in such a way as to introduce deliberate and well-thought-out changes. The current paper aims to focus on the manager’s role by highlighting their personality traits which influence their competencies in times of peace and normality as well as in situations of uncertainty and threat posed by the current pandemic.
Keywords: Manager; Competencies; COVID-19 Pandemic